Industrial Scale Isolation, Structural and Spectroscopic Characterization of Epiisopiloturine from Pilocarpus microphyllus Stapf Leaves: A Promising Alkaloid against Schistosomiasis - Véras, Leiz M. C.; Cunha, Vanessa R. R.; Lima, Filipe C. D. A.; Guimarães, Maria A.; Vieira, Marianne M.; Campelo, Yuri D. M.; Sakai, Vanessa Y.; Lima, David F.; Carvalho Jr, Paulo S.; Ellena, Javier A.; Silva, Paulo R. P.; Vasconcelos, Luciene C.; et al. (PLOS ONE, 2013)
This paper presents an industrial scale process for extraction, purification, and isolation of epiisopiloturine (EPI) (2(3H)-Furanone,dihydro-3-(hydroxyphenylmethyl)-4-[(1-methyl-1H-imidazol-4-yl)methyl]-, [3S-[3a(R*),4b]]), which is an alkaloid from jaborandi leaves (Pilocarpus microphyllus Stapf). Additionally for the first time a set of structural and spectroscopic techniques were used to characterize this alkaloid. EPI has shown schistomicidal activity against adults and young forms, as well as the reduction of the egg laying adult worms and low toxicity to mammalian cells (in vitro). At first, the extraction of EPI was done with toluene and methylene chloride to obtain a solution that was alkalinized with ammonium carbonate. The remaining solution was treated in sequence by acidification, filtration and alkalinization. These industrial procedures are necessary in order to remove impurities and subsequent application of the high performance liquid chromatography (HPLC). The HPLC was employed also to remove other alkaloids, to obtain EPI purity higher than 98%. The viability of the method was confirmed through HPLC and electrospray mass spectrometry, that yielded a pseudo molecular ion of m/z equal to 287.1 Da. EPI structure was characterized by single crystal X-ray diffraction (XRD), 1H and 13C nuclear magnetic resonance (NMR) in deuterated methanol/chloroform solution, vibrational spectroscopy and mass coupled thermal analyses. EPI molecule presents a parallel alignment of the benzene and the methyl imidazol ring separated by an interplanar spacing of 3.758 Å indicating a π-π bond interaction. The imidazole alkaloid melts at 225°C and decomposes above 230°C under air. EPI structure was used in theoretical Density Functional Theory calculations, considering the single crystal XRD data in order to simulate the NMR, infrared and Raman spectra of the molecule, and performs the signals attribution.